Efektivitas Sistem Pengendalian Internal, Teknologi Informasi dan Fraudulent Financial Reporting di LPD - Intan Sri Rahayu, Sang Ayu Kompiang; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2024)
This research aim to examine empirically the effect of effectiveness of internal control system and information technology on fraudulent financial reporting in Lembaga Perkreditan Desa (LPD). The theory used in this research is the theory of Fraud Pentagon. This research conducted in LPDs in Bangli regency with sample used is 62 units which are determined by proportionate stratified random sampling method. The multiple linear regression analysis used as data analysis technique in this research is. The results of this study show that the effectiveness of internal control system has no effect on fraudulent financial reporting. Information technology has a significant negative effect on fraudulent financial reporting. Conclusion based on research results is that LPDs needs to review their internal control system and improve the application of information technology properly in order to reduce  opportunities for fraud. Keywords: Effectiveness of Internal Control System; Information Technology; Fraudulent Financial Reporting; LPD